Uptake of a cell permeable G7-18NATE contruct into cells and binding with the Grb-7-SH2 domain - Ambaye, Nigus D; Lim, Reece C C; Clayton, Daniel J; Gunzburg, Menachem J; Price, John T; Pero, Stephanie C; Krag, David N; Wilce, Matthew C J; Aguilar, Marie-Isabel; Perlmutter, Patrick; Wilce, Jacqueline A (Biopolymers, 2011)
Grb7 is an adapter protein found to be overexpressed in several breast and other cancer cell types along with ErbB2. Grb7 is normally an interaction partner with focal adhesion kinase and in cancer cells also aberrantly interacts with ErbB2. It is thus implicated in the migratory and proliferative potential of cancer cells. Previous studies have shown that the phage display-derived cyclic nonphosphorylated inhibitor peptide, G7-18NATE, when linked to Penetratin, is able to interfere with the interaction of Grb7 with its upstream binding partners and to impact on both cell migration and proliferation. Here we report the synthesis of a biotinylated G7-18NATE covalently attached to just the last seven residues of Penetratin (G7-18NATE-P-Biotin). We demonstrate that this construct is taken up efficiently into MDA-MB-468 breast cancer cells and colocalizes with Grb7 in the cytoplasm. We also used isothermal titration calorimetry to determine the binding affinity of G7-18NATE-P-Biotin to the Grb7-SH2 domain, and showed that it binds with micromolar affinity (K(d) = 14.4 microM), similar to the affinity of G7-18NATE (K(d) = 35.4 microM). Together this shows that this shorter G7-18NATE-P-Biotin construct is suitable for further studies of the antiproliferative and antimigratory potential of this inhibitor.